ANALYSIS OF POLITICAL-CULTURAL TERM TRANSLATION TECHNIQUES IN AL-MAYADEEN NEWS: USING GROK AI - Ariqah Nurussalwa; M. Zacky Mubarok; Muhammad Anas; Darsita Suparno (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study examines Grok AI's translation of Arabic political-cultural terms into Indonesian in Al-Mayadeen news texts. The topic is important because political news translation negotiates cultural meanings, ideology, and political perspectives that may influence readers. Five Arabic-language Al-Mayadeen news articles about Hamas from January to December 2024 were used to extract political-cultural terms for descriptive qualitative translation studies. The analysis classifies micro-level translation techniques using Molina and Albir's framework. Literal translation, borrowing, and established equivalence are Grok AI's most common translation methods, along with modulation, transposition, amplification, generalization, adaptation, and reduction. While these methods improve readability, they also change nuance and ideology, especially in reduction and generalization. This study shows that Grok AI can support political news translation, but human critical evaluation is still needed to ensure cultural sensitivity, ideological accuracy, and contextual integrity.